Gambaran Mikroskopis Nekrosa Sel dan Deplesi Folikel Limfoid Bursa Fabricius Ayam Broiler Pasca Pemberian Probiotik B-mix dan Infeksi Salmonella enteritidis - Eni Rohyati (Politeknik Pertanian Negeri Kupang, 2012)
Profile of Microscopic Necrosis Cells and Depilation of Lymphoid Follicle of Bursa of Broiler after Probiotic B Mix Administration and Enteritic salmonella Infection. Research to determine the incidence of necrosis cells and depletion of lymphoid follicles of bursa of fabricius after administration of B-mix probiotic and infection of Salmonella enteritidis (SE) was performed on 16 of broiler chickens strain abor acress divided into 4 groups; control group (IA), infected by SE (IB), Probiotics without SE infection (2A) and probiotic with infected SE (2B). Probiotic was daily administered at a dose 2 ml/litre of drinking water start at DOC (day old chick) to 6 weeks old chicken. Infection performed at the 4 weeks old chicken with dose 108 CFU/ml of drinking water. Observation and statistical tests has indicate that the groups were administration with B-mix probiotic could be increase the proliferation of lymphocyte cell so that cells of lymphoid follicles is more dense than in the control group, while administration of B-mix probiotic in chickens had been infected by SE, can reduce the incidence of depletion of lymphoid follicles and nekrosa cells.Â Key words: Bacillus, probiotic, Salmonella enteritidis, bursa fabricius, depletion